Penguatan Kelembagaan Dalam Rangka Penyelengaraan Event Rintisan Desa Wisata Doplang - Bambang Guritno; Sapto Supriyanto; Hartoyo Hartoyo (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
This study aims to describe efforts to strengthen village institutions in supporting development programs in Doplang Tourism Village. With the formulation of the problem in this study is how to model village institutional strengthening in supporting development programs in Doplang Tourism Village. This research is a descriptive qualitative research. Data collection methods in this study were literature studies, interviews, field observations, and taking photos/documentation with the data sources in this study using primary data and secondary data. The techniques used in data analysis are data reduction, data presentation, and drawing conclusions. If seen from the village institutional strengthening model, it has been actualized even though there are still institutions that are not well organized, but the success of the implementation of the development program in the Doplang Tourism Village is basically determined by the extent to which the commitment and consistency of village communities work together to build the village. We can see this in village competitions, why not holding village competitions, this should be a lesson for village elements to organize village communities.